ANALISIS FAKTOR INTERNAL DAN EKSTERNAL YANG MEMENGARUHI RENDAHNYA NILAI NUMERASI SISWA KELAS 5 DI SD NEGERI SEROJA - Dwiyanti, Arie; Encep Supriatna (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to analyze the numeracy abilities of grade 5 students and to determine the factors of learning difficulties faced by students as well as solutions that can be used to improve numeracy. This type of research is qualitative research with a case study design. The location of this research is SD Negeri Seroja with the subjects being all students in Class 5. The data collection technique in this research was carried out by observation and interviews. The instruments used were questionnaires and interview guidelines. The results of this research show that 7% of grade 5 students at SD Negeri Seroja have a high level of numeracy ability, 30% have a sufficient level of numeracy ability, 48% have a low level of numeracy ability, and 15% have a very low level of numeracy ability. The factors that cause students' learning difficulties are categorized into two, 1) Internal factors consisting of pessimism and fear of mathematics, laziness in students, and low levels of intelligence, 2) External factors consisting of lack of attention from parents and a poor classroom environment. not inclusive. Solutions that can be used are the use of learning media, adjustments to students' learning styles and additional hours outside of class hours.